Looptempo voorspelt verschillen in niveau van cognitief functioneren - Diesfeldt, Han F.A. (Tijdschrift voor Gerontologie en Geriatrie, 2014)
Bespreking: Mielke, M.M., Roberts, R.O., Savica, R., Cha, R., Drubach, D.I., Christianson, T., Pankratz, V.S., Geda, Y.E., Machulda, M.M., Ivnik, R.J., Knopman, D.S., Boeve, B.F., Rocca, W.A. & Petersen, R.C. (2013). Assessing the temporal relationship between cognition and gait: slow gait predicts cognitive decline in the Mayo Clinic Study of Aging. Journal of Gerontology: MEDICAL SCIENCES, 68, 929–937.